Effect of temperature and chemical pre-treatment on seed germination in papaya (Carica papaya)" - YOGEESHA, H S; BHANUPRAKASH, K; NAIK, L B (The Indian Journal of Agricultural Sciences, 2011)
Alternate temperature of 20 OC for 16 hr and 32 OC for 8 hi- was found optimum for papaya seed germination with 69.5,92.0 and 61.5% germination in fresh seeds of ’Surya’, ’CO 2’ and ’CO 7’ as against 0.0, 1 1.5 and 2.0% respectively in seeds without any treatment at constant temperature of 25 OC. Among the chemical treatments, only GA, could improve the germination significantly at 25 OC. GA, @ 200 ppm was found effective at 25 OC in all cultivars with 85.0, 69.3 and 75.0 per cent germination in ’Surya’, ’CO 2’ and ’CO 7’, respectively. Sarcotesta had no role in inhibiting seed germination. Drying methods also did not affect seed germination significantly. Soaking papaya seeds in GA, @ 200-400 ppm for 48 hr before sowing would greatly improve the germination and emergence in the nursery.